Noise, Information and Fitness in Changing Environments - Pedraza, Juan M.; Garcia, David A.; Pérez-Ortiz, Muriel F. (Frontiers in Physics, 2018)
In this paper we discuss recent results regarding the question of adaptation to changing environments in intermediate timescales and the quantification of the amount of information a cell needs about its environment, connecting the theoretical approaches with relevant experimental results. We first show how advances in the study of noise in genetic circuits can inform a detailed description of intracellular information flow and allow for simplified descriptions of the phenotypic state of a cell. We then present the different types of strategies that cells can use to respond to changing environments, and what a quantitative description of this process implies about the long term fitness of the population. We present an early approach connecting the transmission of information to the average fitness, and then move on to a full model of the process. This model is then simplified to obtain analytical results for a few cases. We present the necessary notation but avoid technical detail as much as possible, as our goal is to emphasize the biological interpretation and significance of the mathematical results. We focus on how carefully constructed models can answer the long-standing objection to the use of information theory in biology based on decision-theoretic considerations of the difference between the amount of information and its fitness value.